The relationship between loan growth, risk, and bank performance: Evidence from Indonesia - Briliane Jovita Jaya; Besse Nur Fathimah Hefri; Astri Suryanti; Trisninik Ratih Wulandari (Universitas Sebelas Maret, 2024)
The crucial role of the banking sector is as an intermediary to give loans or lending to boost a country's economy. Along with advances in technology and digital transformation, lending has become increasingly easier. However, this condition allows for whatever loan growth to affect bank risk or performance. This research investigates the influence of loan growth on risk and bank performance in Indonesia between 2018-2022. The sample for this study consists of all conventional banks in Indonesia. There were 150 data observations from 30 banks in Indonesia. The analysis results indicate that loan growth significantly affects NPL negatively, meaning that loan growth leads to a decrease in NPL. Stringent loan filtering processes, efficient bank risk management programs, and good inspection and supervision can limit the bank's risks associated with loan expansion. Additionally, loan growth negatively and significantly impacts bank performance, especially profitability, indicating that ROA and ROE decline in banks experiencing loan growth. The banking sector needs to be extremely cautious in its loan growth, which can threaten its performance. Moreover, banks should consider maintaining the bank's equity adequacy ratio alongside active loan growth.